Bond Illiquidity and Excess Volatility - Bao, Jack; Pan, Jun (Review of Financial Studies, 2013)
We find that the empirical volatilities of corporate bond and CDS returns are higher than implied by equity return volatilities and the Merton model. This excess volatility may arise because structural models inadequately capture either fundamentals or illiquidity. Our evidence supports the latter explanation. We find little relation between excess volatility and measures of firm fundamentals and the volatility of firm fundamentals but some relation with variables proxying for time-varying illiquidity. Consistent with an illiquidity explanation, firm-level bond portfolio returns, which average out bond-specific effects, significantly decrease excess volatility.